About electrochemical stability and biocompatibility of two types of CoCr commercial dental alloys. Issue 10 (16th February 2016) - Gălăţeanu, B.; Golgovici, F.; Hudita, A.; Stan, M.; Dinescu, S.; Costache, M.; Demetrescu, I.; Popescu, A.
Abstract : The present paper is an investigation of two commercial Co‐Cr dental alloys, named Wirobond 280 and Wirobond C. The two alloys have similar composition; the difference is made by the small amount of Ga and Mn existing in Wirobond 280. The electrochemical behavior of the alloys was tested in the artificial Erikson saliva at different temperatures between 25 and 55 °C. The electrochemical methods used have been the potentiodynamic polarization and the electrochemical impedance spectroscopy. The investigation have been performed in the presence of two different fluoride ions concentrations and permitted to compute corrosion rate and the energy activation. In order to complete the tests the cell response has been studied in vitro. The stability of Wirobond 280 alloy is correlated with the greater cell viability and with a smaller level of ROS in comparison with the Wirobond C alloy. Regarding fluoride doping effect, based on the experimental data, we can conclude that NaF increases the corrosion rate of the Wirobond 280 and decrease the corrosion rate in the case of the Wirobond C. The study established that the Wirobond 280 alloy is the one with best properties. Abstract : Two commercial dental alloys based on CoCr, namely, Wirobond 280 and Wirobond C, the difference being a small amount of Ga and Mn existing in Wirobond 280, were investigated. The stability of Wirobond 280 alloy is correlated with greater cell viability compared with Wirobond C alloy. Regarding fluoride doping effect, NaF increases the corrosion rate of Wirobond 280 and decreases the corrosion rate in the case of Wirobond C.